Scene at a pond - Gordon, John C. (photographer):::Creator::::::::::::
Photograph shows a group of people and a child standing around a pond. Trees, flowers, other plants, and rocks form part of the landscape. Two women stand atop rocks in the water. One shades her face with a hat. Lily pads float on the surface of the water.